Biallelic Mutations in the Otogelin‐Like Gene (OTOGL) Associated With Congenital Non‐Syndromic Sensorineural Hearing Loss in a Chinese Family - Xiang Dai; Jun Li; Xijiang Hu; Wenqian Cai (Molecular Genetics & Genomic Medicine, 2025)
ABSTRACT Background Hearing loss, characterized by significant genetic heterogeneity, is a widespread global disorder. Mutations in the OTOG and OTOGL genes have recently been implicated in non‐syndromic sensorineural hearing loss. However, the mutation spectrum of OTOGL and its functional relevance remain incompletely understood. Methods We investigated a Chinese family with unexplained hearing loss using whole‐exome sequencing. Compound heterozygous mutations in the OTOGL gene were identified and validated through Sanger sequencing. The proband's clinical features were assessed through audiological evaluations, and genotype–phenotype correlation analysis was conducted. Additionally, single‐cell RNA sequencing analysis of the inner ear was performed to explore OTOGL's expression profile in auditory‐related cell types. Results Two compound heterozygous mutations in the OTOGL gene (p.Ile34Val and p.Phe319del) were identified in the proband, a 6‐year‐old boy with moderate congenital hearing loss. These mutations are predicted to be pathogenic and may explain the observed phenotype. Single‐cell RNA sequencing revealed specific OTOGL expression in key auditory‐related cell types, providing insights into its developmental and functional roles in the inner ear. Conclusion The findings have marked implications for molecular diagnosis and genetic counseling, potentially guiding more personalized treatment and intervention strategies in clinical practice.